Mechanical properties and durability of mortar containing fine fraction of demolition wastes produced by selective demolition in South Italy. (15th April 2017) - Colangelo, F.; Cioffi, R.
Abstract: Recycling of construction and demolition waste (CDW) has to be encouraged. Structural concrete and mortar is one of the possible applications, but requires a good quality of the aggregates to be used.The use of wastes treated by mobile plants in the above application is possible only if an accurate selective demolition is conducted. The goal of this study is to produce self-levelling mortars containing high amount of CDW fine fractions that are problematic waste materials. This research investigate the physical and mechanical characteristics of different kind of CDW obtained from selective and traditional demolition techniques. Comparison between the properties of the mixtures obtained from different kind of aggregates offers the possibility to understand the advantages in using selective demolition. The results show that the use of superplasticizer, combined with selective demolition, can improve significantly the mechanical properties of mortars produced with CDW aggregate. In particular aggregate coming from bricks can improve mechanical strength, probably because of their pozzolanic effect.